2020
DOI: 10.3389/fonc.2020.01633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Somatostatin Receptor (SSTR) 2 in Meningioma

Abstract: Somatostatin receptor (SSTR) 2, widely expressed in meningioma, is a G-proteincoupled receptor and can be activated by somatostatin or its synthetic analogs. SSTR2 is therefore extensively studied as a marker and target for the diagnosis and treatment of meningioma. Accumulating studies have revealed the crucial clinical significance of SSTR2 in meningioma. Summarizing the progress of these studies is urgently needed as it may not only provide novel and better management for patients with meningioma but also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 107 publications
(174 reference statements)
1
34
0
Order By: Relevance
“…With an increased incidence in females and ∼100% of meningiomas having somatostatin receptor 2 (SSTR2), ~88% progesterone receptors, ~40% estrogen receptors, and ~40% androgen receptors, it was thought that hormones played a slight role in tumor growth [ 17 , 34 , 35 , 36 , 37 ]. Although previous data assessing the relationship between meningioma risk and oral contraceptives (OCP), hormone replacement therapy (HRT), and reproductive factors have been inconsistent and inconclusive, two meta-analysis and multiple case-control and cohort studies have shown an increased risk associated with HRT [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…With an increased incidence in females and ∼100% of meningiomas having somatostatin receptor 2 (SSTR2), ~88% progesterone receptors, ~40% estrogen receptors, and ~40% androgen receptors, it was thought that hormones played a slight role in tumor growth [ 17 , 34 , 35 , 36 , 37 ]. Although previous data assessing the relationship between meningioma risk and oral contraceptives (OCP), hormone replacement therapy (HRT), and reproductive factors have been inconsistent and inconclusive, two meta-analysis and multiple case-control and cohort studies have shown an increased risk associated with HRT [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The function of SST has been profoundly investigated in previous studies using its receptors (SSTR1-SSTR5) as mediators (25). Among all SST receptors, SSTR2 is the most abundant (19). Additionally, SSTR2 is expressed in human pancreatic tissue, but could be loss in pancreatic cancers and derived cell lines (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, overexpression of PIK3R3 can support the growth of GBM cells by engaging IGF2 signaling in vitro, indicating that PIK3R3 is an oncogene in glioma [ 68 ]. Somatostatin receptor 2 (SSTR2) is the family of G protein-coupled receptors and is widely expressed in solid tumors [ 69 , 70 ]. SSTR2 is also expressed in inflammatory and lymphocytes cells, regulating the proliferative and secretory responses of these cells [ 69 ].…”
Section: Discussionmentioning
confidence: 99%